2018
DOI: 10.1051/0004-6361/201731807
|View full text |Cite
|
Sign up to set email alerts
|

Cold prominence materials detected within magnetic clouds during 1998–2007

Abstract: Context. Coronal mass ejections (CMEs) are intense solar explosive eruptions, and they are frequently correlated with prominence eruptions. Previous observations show that about 70% of CMEs are associated with prominence eruptions. However, there are only a handful of reported observations of prominence plasma materials within interplanetary CMEs (ICMEs), which are the interplanetary manifestations of CMEs. Moreover, approximately 4% of ICMEs exhibit the presence of prominence materials, and approximately 12% … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…The work reported that magnetic clouds exhibit higher ionic charge states than non-magnetic clouds. In addition, statistical results demonstrated that fast magnetic clouds have higher charge states and relative elemental abundances (except the C/O) than slow ones (Owens, 2018;Huang et al, 2020), and cold prominence plasmas with lower charge states can be detected within ICMEs near 1 au (Lepri and Zurbuchen, 2010;Gilbert et al, 2012;Sharma and Srivastava, 2012;Wang, Feng, and Zhao, 2018;Feng et al, 2018). Zurbuchen et al (2016) performed a comprehensive analysis of the elemental abundances of 310 ICMEs on Richardson and Cane's catalog from 1998 March to 2011 August (Richardson and Cane, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The work reported that magnetic clouds exhibit higher ionic charge states than non-magnetic clouds. In addition, statistical results demonstrated that fast magnetic clouds have higher charge states and relative elemental abundances (except the C/O) than slow ones (Owens, 2018;Huang et al, 2020), and cold prominence plasmas with lower charge states can be detected within ICMEs near 1 au (Lepri and Zurbuchen, 2010;Gilbert et al, 2012;Sharma and Srivastava, 2012;Wang, Feng, and Zhao, 2018;Feng et al, 2018). Zurbuchen et al (2016) performed a comprehensive analysis of the elemental abundances of 310 ICMEs on Richardson and Cane's catalog from 1998 March to 2011 August (Richardson and Cane, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the predicted observational characteristics of interplanetary remnant prominence materials should have low temperature, high density, and low ionic charge states, and these signatures can be taken as evidence to identify prominence material. However, the observational low temperature and high density characteristics can be modified by propagation effects when solar wind flows propagate from the Sun to the Earth (Janvier et al 2014;Wang et al 2018). The new high-density regions can be formed, and original low-temperature regions also can disappear near 1 AU through the non-uniform expansion of magnetic structures in the solar wind (Wang et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…However, the observational low temperature and high density characteristics can be modified by propagation effects when solar wind flows propagate from the Sun to the Earth (Janvier et al 2014;Wang et al 2018). The new high-density regions can be formed, and original low-temperature regions also can disappear near 1 AU through the non-uniform expansion of magnetic structures in the solar wind (Wang et al 2018). The ionic charge states in the interplanetary media mainly depend on their solar source temperature because the solar wind ion charge states are nearly frozen near the Sun (Heidrich-Meisner et al 2016;Wang & Feng 2016;Wang et al 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, eruptive prominences can be traced into the upper corona to become CME bright cores (House et al, 1981;Illing & Athay, 1986;Gopalswamy et al, 1998). Cold material evidently belonging to remnants of eruptive filaments is also detected within interplanetary CMEs (ICMEs), which are interplanetary manifestations of CMEs (Lepri & Zurbuchen, 2010;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%